2003
DOI: 10.3989/scimar.2003.67n1113
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype supporting <i>Mugil curema</i> Valenciennes, 1836 and <i>Mugil gaimardianus</i> Desmarest, 1831 (Mugilidae: Teleostei) as two valid nominal species

Abstract: SUMMARY: In this study, we present the karyotypic features of two taxa, curema and gaimardianus (genus Mugil), supposed to be synonyms by some authors. Their cytogenetic differences are conspicuous and unambiguous, providing evidence that Mugil curema and Mugil gaimardanus are two valid nominal species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 6 publications
0
30
0
3
Order By: Relevance
“…Specifically considering mullet in the area, through different mtDNA markers (Fraga et al, 2007;Heras et al, 2009;BOLD), at least three different clusters can be identified within M. curema, which also include other mullet species. Similarly, in the same species complex, from a cytogenetic point of view, in addition to the two cytotypes described above, it has to be mentioned the chromosome complement of M. rubrioculus, formerly considered M. curema ( Nirchio et al, 2003Nirchio et al, , 2007, which has allowed to confirm it as a valid species. As one M. curema population from Brazil (Nirchio et al, 2005) exhibits a chromosome complement with 2n=28 (Cytotype 1) apparently similar to the one described for M. incilis from Brazil (Pauls et al, 1998;Galetti et al, 2000;Netto et al, 2007), further sampling of Brazilian specimens is necessary to check out whether or not they belong to a different species from M. curema.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically considering mullet in the area, through different mtDNA markers (Fraga et al, 2007;Heras et al, 2009;BOLD), at least three different clusters can be identified within M. curema, which also include other mullet species. Similarly, in the same species complex, from a cytogenetic point of view, in addition to the two cytotypes described above, it has to be mentioned the chromosome complement of M. rubrioculus, formerly considered M. curema ( Nirchio et al, 2003Nirchio et al, , 2007, which has allowed to confirm it as a valid species. As one M. curema population from Brazil (Nirchio et al, 2005) exhibits a chromosome complement with 2n=28 (Cytotype 1) apparently similar to the one described for M. incilis from Brazil (Pauls et al, 1998;Galetti et al, 2000;Netto et al, 2007), further sampling of Brazilian specimens is necessary to check out whether or not they belong to a different species from M. curema.…”
Section: Discussionmentioning
confidence: 94%
“…The peculiar cytotaxonomic features of Mugil incilis might constitute a clear cut diagnostic tool in showing species boundaries, which might be very helpful in identifying cryptic species in the M. curema complex, as already occurred (Nirchio et al, 2003; on the other hand, present data indicates that it would be useful to add cytogenetic data on the other Mugilidae species which have yet to be described and to parallely increase the molecular database on them, in order to clarify the karyoevolutive patterns and the phylogenetic relationships within the family.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Mugil sp. (formerly gaimardianus, suppressed name by the International Commission on Zoological Nomenclature, ICZN 1787) and M. curema were recently identified as separate species on the basis of their karyotype (Nirchio et al, 2003), which reveals the importance of karyotypic studies in solving taxonomic problems among closely related species.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the FISH observations revealed very week additional signals in the interstitial position in two chromosome pairs, contrasting with the results described by Wasko, Galetti (2000) for other Brycon species. The FISH technique using 18S rDNA sequences has identifi ed a higher number of major ribosomal cistrons than the Ag-NOR technique in several species of fi sh: Salmo trutta Linnaeus, 1758 (Pendás et al, (Nirchio et al, 2003), Lebias fasciata Valenciennes, 1821 (Tigano et al, 2004) and Triportheus venezuelensis Spix, 1829 (Nirchio et al, 2007). Even though these signals may be technical artifacts, they would also represent chromosome regions with NORs that are usually unexpressed, due to DNA methylation and gene silencing related to positional effects induced by heterochromatin (C-bands) and/or telomeres, as suggested by Guillén et al (2004).…”
Section: Comp Cytogenet 2010 4(2)mentioning
confidence: 99%